Delivering Clinical Pastoral Education (CPE) Remotely: Educators' Views and Perspectives During the COVID-19 Pandemic and Beyond. (September 2022) - Szilagyi, Csaba; Tartaglia, Alexander; Palmer, Patricia K.; Fleenor, David W.; Jackson-Jordan, Elizabeth; Knoll Sweeney, Sarah; Slaven, James E.
Many Clinical Pastoral Education programs pivoted to remote delivery during the COVID-19 pandemic. Our survey explored educators' preparedness, self-efficacy, and views regarding remote Clinical Pastoral Education. Few respondents were either very (14.2%) or not at all (16.5%) prepared. Most were confident facilitating remote learning (69.8%–88.5%), believing remote Clinical Pastoral Education can achieve outcomes equivalent to in-person (59.1%). Six qualitative themes emerged: educator development, educator challenges, remote Clinical Pastoral Education efficacy, remote group dynamics, clinical practice/supervision implications, and benefits and opportunities.